Introduction of IMRT in Macedonia: Optimizing the MLC parameters - Lukarski, Dushko; Ristova, Mimoza (Institute of Physics, Faculty of Natural Sciences and Mathematics, "Ss. Cyril and Methodius University", Skopje, Macedonia, 2012)
Intensity modulated radiotherapy (IMRT) for the Varian Eclipse Treatment Planning System (TPS) requires optimization of the values of two parameters of the Multi Leaf Collimator (MLC) – the transmission of the MLC and the so called Dosimetric Leaf Gap (DLG). This paper describes the optimization of those parameters for one of the linear accelerators at the University Clinic for Radiotherapy and Oncology in Skopje. The starting values for the MLC parameters were determined by dose measurements with ionization chambers. Those measured values were introduced in the TPS and an IMRT test plan was created. The acquired test plan was used for irradiation of the two-dimensional chamber array “MatriXX”, and for comparison of the measured results with the corresponding results calculated by the TPS. By iteratively changing the two MLC parameters we optimized their values, so that the calculation corresponds to the measurement as much as possible. The final results of the optimization were introduced in the TPS thus enabling calculation of IMRT plans and proceed towards the phase of clinical introduction of this radiotherapy technique.
Keywords: IMRT; MLC; DLG; MLC transmission